Decision Making System for Educator Recruitment at IP Daarul Arqam Private Junior High School using Simple Additive Weighting Method - Anzani, Nurul; Wayahdi, M. Rhifky; Purwawijaya, Ellanda (Journal of Technology and Computer, 2024)
An institution can work well to achieve its goals which are determined by many factors. Teachers play an important role in improving the life of a nation. Teachers have great obligations and responsibilities in terms of educating the nation's children. Therefore, a school has several criteria in selecting educators. For this reason, accuracy and examination are needed in selecting educators to get qualified teachers. By using a Web-based decision support system the problems faced by foundations or schools can be overcome, so that subjectivity in decision making can be reduced. This system can integrate data on prospective educators from various sources, such as education, work experience, expertise, and others. In addition, this system can also apply predetermined decision-making methods, such as the Simple Additive Weighting (SAW) method. By using this system, decision makers can easily access and analyze prospective educators' data comprehensively. They can also see the results of ranking prospective educators based on relevant criteria. This allows decision makers to make more objective and informed decisions in determining teaching staff. With this application, it can make it easier to make decisions on determining teaching staff.